2017
DOI: 10.1080/0284186x.2016.1269193
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing therapy and progressive resistance training in head and neck cancer patients undergoing radiotherapy treatment: randomized control trial protocol and preliminary data

Abstract: Background: Head and neck cancer (HNC) patients are often challenged by treatment induced dysphagia and trismus. Traditionally, rehabilitation is initiated when loss of function has already occurred. There is increasing evidence that it is of benefit to patients to initiate an early rehabilitation process before and during treatment. HNC patients have a unique set of functional challenges such as preand post-treatment dysphagia, pain and weight loss. The aim of the trial is to investigate the effects of swallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 25 publications
(28 reference statements)
0
39
0
2
Order By: Relevance
“…(31, 32) One study(27) did not report an age range or mean. Including all studies that reported the age range and mean,(2426, 2830, 33) the collective age range for this review was 21–94, and the mean was 60.4 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(31, 32) One study(27) did not report an age range or mean. Including all studies that reported the age range and mean,(2426, 2830, 33) the collective age range for this review was 21–94, and the mean was 60.4 years.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies(17, 25, 27, 34) completed retrospective studies earning a JAMA score of 3. Five studies(24, 26, 28, 30, 33) earned a JAMA quality rating score of 4 and used the following designs: prospective cohort,(24) case-series(26, 28, 33) and pilot study. (30)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations